FISCAL POLICY AND OUTPUT VOLATILITY:EMPIRICAL EVIDENCE FROM BULGARIA - Todorov, Ivan; Ivanova, Lyubov (Revista Inclusiones, 2020)
The objective of this paper is to investigate the relationships between Bulgaria’s output gap, on the one hand, and Bulgaria’s fiscal balance and changes in government expenditure, on the other hand. An autoregressive distributed lag model (ARDL), a vectorautoregression (VAR) and quarterly seasonally and calendar adjusted Eurostat data for the period 1999-2020 are employed. The research results indicate that there is a long-term equilibrium connection but no short-run link between the output gap and the fiscal balance. The study results imply that the output gap affects but is not affected by the changes in government expenditure. Bulgaria’s fiscal policy impacts the cyclical position of the Bulgarian economy in the long term but not the short run. Neither the fiscal balance nor the changes in government expenditure can be used to smooth out the short-run fluctuations of the Bulgarian economy. The changes in Bulgaria’s government spending are not discretionary but driven by output volatility.